VD_FINDINFO Jug / 2022 / 287 vom 10. März 2022 - VD Tribunal cantonal (2022)
AVOCAT, INDEMNITÉEN GÉNÉRAL, PROCÉDURE ÉCRITE, FRAIS JUDICIAIRES, CRÉANCE COMPENSANTE | 71 al. 1 CP, 426 al. 2 CPP (CH), 429 al. 1 let. a CPP (CH)